Say hello to my little friend… micronutraceuticals in neuroenergetics, neuronal health, and neurodegenerative diseases - Mason, Shayne (Frontiers in Neuroscience, 2025)
Vitamins and minerals (micronutraceuticals) maintain good health. However, the specific effects of these micronutraceuticals on brain health are often overlooked, or not even known. In this review, an overview of the direct and indirect effects of micronutraceuticals on brain energy metabolism (neuroenergetics) and neuronal health is provided. Thereafter, a holistic summary of the existing studies that have shown the impact of micronutraceuticals on neurodegenerative diseases. Lastly, this review concludes by identifying several research gaps that remain and provides suggestions for future research on these hot topics.